Planejamento estratégico: uma proposta para a empresa Rafaelli Arte em Velas - Santin, Patrícia (2018)
The labor market is constantly changing and this causes companies to work planning their actions, in order to remain highly competitive in the market they are in, taking advantage of opportunities to achieve their goals and increase their profitability. Strategic Planning is one of the tools used by management to assist in decision making, providing the organization with possibilities to improve its strengths and reduce or eliminate its weaknesses, and seize the opportunities that arise from the market, to face the difficulties and threats that may arise. The better planned and managed the organization is, the more efficient and with greater chances of success it will be. This research animed to propose a strategic plan for the company Rafaelli Arte em Velas Ltda., which has been active in the market of Chapecó since 2016. The research is characterized as descriptive, qualitative approach, carried out through company documents, literature and semi-structured interview, and observational analysis. It is also classified as an applied research field, case studies, and documentary. Therefore, this research has resulted in a strategic planning proposal for the company, with the definition of business, the target audience and the profile of the company, in the review of the mission and vision, development of analysis the internal and external environments, the values, the general objective of the company, as well as strategies and action plan in order to achieve the results as planned.